2020
DOI: 10.1111/dth.14041
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes, behaviors, and opinions about non‐pharmacological agents in patients with tinea pedis

Abstract: Tinea pedis affects the life quality distinctly and patients those with a prolonged disease often resort to non-medical methods. We sought to evaluate patients' knowledge about tinea pedis and approaches to the non-pharmacological agents. A crosssectional study was conducted on 152 patients with tinea pedis who answered the survey between July and November 2019. Demographic and clinical features, patients' attitudes, behaviors, and opinions about non-pharmacological treatments related to tinea pedis were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…However, Polat reported cologne, saltwater, vinegar and henna as common applicants in his study population. 20 But most of the patients (80%), experienced no relief after application of these substances in this study.…”
Section: Practicesmentioning
confidence: 56%
See 1 more Smart Citation
“…However, Polat reported cologne, saltwater, vinegar and henna as common applicants in his study population. 20 But most of the patients (80%), experienced no relief after application of these substances in this study.…”
Section: Practicesmentioning
confidence: 56%
“…This was also highlighted by Polat et al in 2019 who reported that education and knowledge have significant correlation with presence and absence of tinea pedis in their study subjects. 20 Similarly, Farida et al, also saw an increase of disease alleviating attitude and practices from 38% to 67% after counselling and targeted education of the affected population. 21 Limitation of this study is that it does not correlate the educational, and socioeconomic status of study subjects with their knowledge, attitude and practices regarding dermatophytic infection spread and further puts forward the next research question in this area.…”
Section: Practicesmentioning
confidence: 95%
“…The chronic nature of tinea pedis is caused by a fungal infection, with inflammation being the prominent clinical manifestation. , Therefore, anti-inflammatory treatment has emerged as a pivotal therapeutic indicator for tinea pedis. Key inflammatory factors mediating skin damage in tinea pedis include TNF-α, IL-1β, IL-6, and IL-10.…”
Section: Resultsmentioning
confidence: 99%
“…rubrum, and C. albicans. , To assess the antifungal efficacy of SA/FK13-a1@GelMA MNs, we conducted antifungal ratio and inhibition zone tests. As depicted in Figure A,B, initial assessments of GelMA MNs loaded with FK13-a1 showed significant antifungal activity against T.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation